Becoming an 'Adaptive' Expert: Investigating student knowledge transfer and metacognitive activities at college CS departments and at coding bootcamps. - BURKE, QUINN; BAILEY, CINAMON SUNRISE (Communications of the ACM, 2020)
The article discusses the development of adaptive expertise (AE) in computer programming education in students in undergraduate computer science (CS) programs and what are referred to as coding boot camps. It also discusses metacognitive activities, student knowledge transfer, and learner adaptability.